2015
DOI: 10.1177/1078390314566882
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Maternal Postpartum Psychological State and Breast Milk Secretory Immunoglobulin A Level

Abstract: These results indicate that the maternal psychological state may affect the immune properties of breast milk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 43 publications
(50 reference statements)
3
41
1
1
Order By: Relevance
“…In addition to TGFβ2, three studies investigated the association between postpartum depression and milk sIgA levels, with one study reporting an increase of sIgA levels in depressed mothers (Hart et al, 2004), one study reporting no correlation (Groër et al, 1994) and one reporting a significant decrease of sIgA levels in depressed mothers (Kawano and Emori, 2015). Results from the last study are in line with previous evidence, showing a decrease in sIgA levels in faecal samples of children who were breastfed by depressed mothers (Kang et al, 2017).…”
Section: Immune Componentssupporting
confidence: 80%
See 1 more Smart Citation
“…In addition to TGFβ2, three studies investigated the association between postpartum depression and milk sIgA levels, with one study reporting an increase of sIgA levels in depressed mothers (Hart et al, 2004), one study reporting no correlation (Groër et al, 1994) and one reporting a significant decrease of sIgA levels in depressed mothers (Kawano and Emori, 2015). Results from the last study are in line with previous evidence, showing a decrease in sIgA levels in faecal samples of children who were breastfed by depressed mothers (Kang et al, 2017).…”
Section: Immune Componentssupporting
confidence: 80%
“…Two studies did not find any significant correlation between maternal state or trait anxiety and sIgA (Groër et al, 1994), and state anxiety and sIgA milk levels (Hart et al, 2004). However, one study found a negative association between postpartum state and trait anxiety scores, and sIgA milk levels (Kawano and Emori, 2015). This is in contrast with results previously described where only state anxiety, but not trait anxiety, was associated with high ions levels in milk (Ozbek et al, 2008;Serim Demirgoren et al, 2017).…”
Section: Immune Componentsmentioning
confidence: 59%
“…We found no statistical interaction between the maternal distress trajectory variable and breastfeeding status in the association with fecal sIgA in study infants. However, the breastfed infant may not be impervious to maternal mood, as lower sIgA levels have been reported in the breast milk of mothers who experience anxiety . This observation may partially explain our findings in older breastfed infants.…”
Section: Discussionmentioning
confidence: 50%
“…SIgA serves as a defense against infections, and low salivary sIgA levels are associated with increased likelihood of illness (Jemmott & McClelland, ; Volkmann & Weekes, ). Numerous behavioral immunology studies in adults have shown that psychological distress and stressful experiences reduce breast milk (Groer, Davis, & Steele, ; Kawano & Emori, ) and salivary sIgA (Engeland et al, ; Graham, Chiron, Bartholomeusz, Taboonpong, & Brooy, ; Phillips et al, ; Segerstrom & Miller, ) while the developmental literature consistently shows maternal well‐being is a primary regulator of child development (e.g., Morris, Silk, Steinberg, Myers, & Robinson, ). Our findings extend these two fields revealing the importance of maternal well‐being for infant immunity.…”
Section: Discussionmentioning
confidence: 99%